Chinese institutional innovation and privatization from below - Naughton, Barry (American Economic Review, 1994)
One of the most distinctive features of China's transition to a market economy has been the role played by rural township and village enterprises (TVE's). In the face of sustained rapid growth of TVE's, the share of total industrial output produced by state-owned enterprises (SOE's) has fallen below half, despite steady state-sector growth and the absence of significant privatization. Yet most TVE's are collectives, a form of publicly owned enterprise. This feature seems to make them unique: in no other transitional economy has public ownership played such a dynamic role. China presents the unusual picture of an economy that has made a transition to a primarily market economy, but in which publicly owned enterprises still produce the bulk of manufacturing output. Surprisingly also, the collective ownership form does not have a precise legal definition in China, leading to some uncertainty about ultimate property rights. Martin Weitzman and Chenggang Xu (1993) point out that public ownership with vaguely defined ownership ought to represent a recipe for economic disaster. To them, TVE success suggests instead advantages to the internal institutional form of TVE's, which are seen to facilitate cooperation through implicit contracts among community members locked into an ongoing relationship. Victor Nee (1992) advances a similar interpretation, arguing that long-time community residents create forms of income-sharing that may be optimal in the absence of an independent legal system. An alternative, perhaps complementary, view is presented here. The success of TVE's, I argue, is due largely to a set of external conditions to which TVE's are an effective adaptation. TVE's are responses to one of the most distinctive characteristics of the Chinese transition as a whole: the early creation of product markets, which exist for a prolonged period without well-developed markets for factors of production or assets. TVE's are a flexible and effective but basically ordinary adaptation to this environment.